Auxin‐mediated relationships between apple plants and root inhabiting fungi: impact on root pathogens and potentialities of growth‐promoting populations. (4th November 2014) - Manici, L. M.; Kelderer, M.; Caputo, F.; Mazzola, M.
<x xml:space="preserve">Abstract</x> This study aimed to elucidate the relationship between plant hosts and root‐colonizing fungi recovered from apple orchard soils that had been replanted over multiple generations. Functional relationships of three groups of filamentous fungi (Ceratobasidium sp., Cylindrocarpon‐like group and Fusarium acuminatum) with apple rootstocks were evaluated in plant growth bioassays. The Cylindrocarpon‐like group and Ceratobasidium sp. showed a relationship with the host plant varying from pathogenic to commensal through to mutualistic for the latter group, while that of F. acuminatum tended to be mutualistic. Seven fungal isolates of each group, which induced the highest plant growth in bioassays, were evaluated for auxin (IAA) and gibberellin (GA3 and GA4) production in culture filtrate. All isolates of F. acuminatum as well as most of those of the Ceratobasidium sp. and Cylindrocarpon‐like groups produced IAA in culture filtrate. IAA production was evaluated for additional isolates of endophytic fungal species from fruit tree orchards and the functionality of IAA was confirmed by growing in vitro micropropagated plantlets of apple rootstock on MS medium supplemented with fungal culture filtrate. Findings from this study may explain the difficulty in defining the precise role of diverse root‐colonizing fungal populations in replant disease aetiology of fruit tree orchards. However, the results demonstrate the presence of a positive and widely available biotic component of the orchard soil biology that may be exploited for the benefit of tree growth and production.